2015
DOI: 10.1016/j.intmar.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adopting and Using a Brand's Mobile Application on Customers’ Subsequent Purchase Behavior

Abstract: Mobile applications (apps) have become an important platform for brands to interact with customers, but few studies have tested their effects on app adopters’ subsequent brand purchase behavior. This paper investigates whether adopters’ spending levels will change after they use a brand's app. Using a unique dataset from a coalition loyalty program with implementations of propensity score matching and difference-in-difference-in-difference methods, we compare the spending levels of app adopters with those of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 45 publications
3
170
0
4
Order By: Relevance
“…Kim, Wang, and Malthouse (2015) found that repeated use of the m-commerce applications (high habit strength) leads to increases in future m-commerce spending. Lin and Wang (2006) developed and validated an m-commerce customer loyalty model.…”
Section: Habitmentioning
confidence: 99%
“…Kim, Wang, and Malthouse (2015) found that repeated use of the m-commerce applications (high habit strength) leads to increases in future m-commerce spending. Lin and Wang (2006) developed and validated an m-commerce customer loyalty model.…”
Section: Habitmentioning
confidence: 99%
“…Due to the high customer involvement in social media apps, many companies have developed their smart phone apps to communicate and advertise their products to their customers (Kim, Wang, & Malthouse, 2015). About 60% of smart phone owners have encountered smart phone advertising while 69.5% have viewed smart phone advertisements, and 62.3% have purchased advertised products or services (Kim & Han, 2014).…”
Section: Social Media Advertisingmentioning
confidence: 99%
“…Another 13% stated to have plans to introduce a mobile application in the forthcoming period, having in mind that applications became an important platform for brands to interact with the customers, and whose adoption and continued use contributes to the increase in future spending [30].…”
Section: Advertisersmentioning
confidence: 99%